Assessing and Comparing Data Imputation Techniques for Item Nonresponse in Household Travel Surveys. Issue 1 (January 2023) - Budhwani, Alikasim; Lin, Tina; Feng, Devin; Bachmann, Chris
This research provides a comparative assessment of data imputation techniques for item nonresponse in household travel surveys. Using the Transportation Tomorrow Survey (TTS) data for the Region of Waterloo in Ontario, Canada, a series of synthetic datasets are generated with varying amounts of missing data, while preserving the respective proportions of missing items and missing item combinations in the original survey data. Then, the performances of six different imputation techniques are compared. The six different imputation techniques include two simple imputation techniques (mode and hot-deck), three discriminative models (logistic regression, multi-layered perceptron, support vector machines) and one generative model (autoencoder). This assessment compares these techniques, as well as the impact of the proportion of item nonresponse in the dataset through their repeated application to multiple synthetic datasets. Results show that the machine/deep learning techniques (both generative and discriminative) not previously applied to household travel survey data outperform their simple imputation counterparts. Overall, the accuracy of travel household survey data imputation is shown to depend on many factors, including the technique employed, the dimensionality of the missing item, and the hypertuning of the technique (if applicable), but not on the amount of missing data in these experiments. This research should prove beneficial to practitioners who often confront item nonresponse in their household travel survey data by providing evidence and recommendations to support the selection and implementation of a data imputation technique. The research methodology also provides a repeatable procedure for future researchers to test data imputation techniques on their own datasets.